(untitled) (International Journal of Studies in Nursing, 2019)
Background: Patients on medical-surgical units such as orthopedic-neurology are vulnerable for delayed recognition of physiological deterioration. Therefore, they are at increased risk of incurring a resuscitation event. Volume-based nurse staffing does not consider the necessity of nursing care that is individualized to the patient needs. Purpose: The purpose of this study was to implement an acuity tool to evaluate the number of resuscitation event occurrences on an Orthopedic-Neurology Unit. Method: A quasi-experimental, non-randomized, quality improvement project was implemented on a 32-bed Orthopedic/Neurology Unit over a three-month period, comparing resuscitation event occurrences with the use of the acuity tool and the group‘s performance without the acuity tool. Analysis: For data analysis, a Chi-square test-for-independence was used with a 2x2 contingency table, for variance of the number of patient resuscitation event occurrences with and without the use of the tool. Data were examined and combined for the three months before and after the use of the tool. When compared to the three months that the tool was employed, it yielded a 1% difference, with a 33% relative risk reduction. Results: Results indicated support for clinical significance. The use of the acuity tool demonstrated a significant decrease in the number of occurrences from 9 to 2 to 0 for each successive month of the project on the Orthopedic/Neurology Unit.